A presença da literatura/cultura portuguesas em periódicos paulistas - 1900-1922 - Feitosa, Rosane Gazolla Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Partindo-se do pressuposto de que existe uma interligação, por meio da presença da literatura/cultura portuguesa, entre Portugal e a cidade de São Paulo – no período de 1900-1922, caracterizado ainda como pré-modernista brasileiro –, a proposta deste texto dirige-se ao comentário de alguns periódicos (O Estado de S. Paulo; A Vida Moderna; O Pirralho), visto que “[...] há uma história da literatura que se projeta na cidade de S. Paulo; e há uma história da cidade de S. Paulo que se projeta na literatura.” (CANDIDO, 1975). Assim, pretende-se verificar como a presença da literatura/cultura portuguesa (principalmente autores canônicos do século XIX) repercutiu na vida social e intelectual da cidade de São Paulo, para melhor compreensão das formas de sociabilidade, bem como a caracterização das diferentes etapas percorridas pela literatura brasileira em São Paulo.

In light of the presence of Portuguese literature and culture, and with the presumption that a link exists between Portugal and the City of Sao Paulo from 1900 to1922, characterized as a pre-modernist epic, the aim of this text directs itself toward the analysis of a selection of periodicals published in Sao Paulo at that time: O Estado de S. Paulo; A Vida Moderna; O Pirralho. From the quotation: “there is a history of literature that projects itself into the City of Sao Paulo; and there is a history of the City of Sao Paulo that projects itself into literature (CANDIDO, 1975), a verification will be made of how the presence of Portuguese literature and culture (especially 19th century canonical authors) spread into the social and intellectual life of the City of Sao Paulo, to better understand the forms of sociability as well as the characterization of the different stages Brazilian literature passed through in the City of Sao Paulo.
Portuguese literature and culture in periodicals published in the City of São Paulo - 1900-1922
Keywords: Periodical; Portuguese Literature; History of Literature; Periódico; Literatura Portuguesa; História da Literatura